Cell-free DNA From Pleural Effusion Samples: Is It Right for Molecular Testing in Lung Adenocarcinoma? - Mokánszki, Attila (Pathol Oncol Res, 2021)
Pathogenic molecular features gained specific significance in therapeutic decisions in lung carcinoma in the past decade. Initial and follow up genetic testing requres appropriate amounts and quality of tumor derived DNA, but tumor sampling, especially for disease monitoring is generally limited. Further to the peripheral blood (PB), samples from pleural fluid, accumulating in diverse lung processes might serve as an alternative source for cell-free DNA (cfDNA) for genetic profiling. In our study, cfDNA isolated from the pleural effusion and from the PB, and genomic DNA (gDNA) obtained from tissue/cellular samples were analyzed and compared from altogether 65 patients with pulmonary disease, including 36 lung adenocarcinomas. The quantity of effusion cfDNA yield appeared to be significantly higher compared to that from simultaneously collected PB plasma (23.2 vs. 4.8 ng/μl, p < 0.05). Gene mutations could be safely demonstrated from the effusion cfDNA fraction obtained from adenocarcinoma patients, 3/36 EGFR, 9/36 KRAS and 1/36 BRAF gene variants were detected. In this series, 9/13 samples showed an effusion+/plasma-mutational status, while only 1/13 samples presented with the opposite findings (effusion-/plasma+). gDNA analysis from sediment cell blocks from the identical effusion sample was surprisingly ineffective for lung adenocarcinoma profiling due to the low DNA yield. In conclusion, the cell free supernatant of pleural effusions appears to concentrate cancer derived cfDNA and seems to be particularly suitable for serial genotyping of pulmonary adenocarcinoma.